The effects of various modes of absenteeism problem in school on the academic performance of students in secondary schools - Yahaya, Azizi; Ramli, Jamaluddin; Hashim, Shahrir; Ibrahim, Mohd. Ali; Abd. Kadir, Hamdan; Boon, Yusof; Raja Abd. Rahman, Raja Roslan (EurojournalPublication, 2010)
This article highlights some of the major research findings regarding the problem of school discipline such as truancy and demonstrates why it is important that schools and communities work to prevent and reduce absenteeism. Beside that this article demonstrated the types of truant and activities done during truant against academic achievement among the lower secondary students.. The respondents for this study were 80 students from form 1, 2 and 3. They were randomly chosen as respondents through simple random sampling. The data collected is analyzed by using the Statistical Package for Social Science for Windows (SPSS 11.5) to find the mean, frequency and standard deviation by using descriptive statistics. The findings showed that the causes of truant are at the medium level and types of truant are at the low level. Activities done during truant such as helping the family, joining the negative groups, crime are at the low level and working part-time together with loafing are at the medium level